Penerapan Akad Wakalah pada Sistem Letter of Credit Syariah - Zhulis Anggraeni Ramadanti (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
The existence of a letter of credit that is truly in accordance with sharia principles has been awaited by Muslim entrepreneurs who want to carry out their religious values ​​throughout their lives. Conventional L/C is considered as in sharia L/C because the practice still applies the interest system. The Sharia L/C Regulation has been in Law no. 21/2008 regarding Sharia Banking, in article 19 p. 34/DSN-MUI/IX/2002 concerning Sharia Import L/C and MUI National Sharia Council Fatwa No. 35/DSN-MUI/IX/2002 concerning Sharia Export L/C. Sharia L/C can apply several contract contract models, such as: wakalah bi al-ujrah, qard, murabahah, salam/istisna', musharaka, hawalah and al-bai. Of the various model contracts that can be applied to Sharia L/C, wakalah bi al-ujrah and murabahah are considered the most efficient, the safest, and the least risky. Keywords: Letter of Credit, Application of Contract, Wakalah Contract